The Mediating Influence of Job Satisfaction on Employee Performance at PT. Kita Serba Digital Co. - Eduardo, Farrell Ionwyn; Nelly (Technology, Business and Entrepreneurship, 2024)
Job satisfaction is a key determinant of organizational success. This study aims to measure the impact of job satisfaction as a mediator between employee performance and digital literacy or entrepreneurial culture. This study used a questionnaire as a quantitative methodology. The data was collected by utilizing the census sampling technique. A total of 51 full-time employees and interns from PT Kita Serba Digital Co. were selected as respondents for this study. Multiple regression analysis was used, and the data was processed using SPSS 26 software. This study revealed that digital literacy and entrepreneurial culture has a significant effect on employee performance. In addition, job satisfaction was determined to have a significant mediating effect on employee performance. Based on these findings, PT Kita Serba Digital Co. should focus on enhancing job satisfaction and digital literacy to improve employee performance. However, the results may be difficult to generalize due to the specific scope of the study.